Whole Farm, Profit Objective Pricing - Langemeier, Larry N. (My University, 1997)
This publication is meant to help producers calculate a profit objective price for their commodities in any given year based on that year's farm mix of crops and livestock and on historical price and production data.
MF1101_1997_10
Keywords: MF1101; Economics; MF